Time Theft in the Los Angeles Retail Sector: The Need for New Labor Standards and a Fair Workweek. (March 2022) - Sharma, Preeti; Stepick, Lina; Shadduck-Hernández, Janna; Waheed, Saba
We argue that employers subject workers to time theft by controlling workers' time—both on and off the clock. Time theft considers employer control of workers' time without the promise of pay through unstable scheduling practices as well as beyond their scheduled work hours . We develop a typology of time theft through a discussion of survey and workshop data with retail workers in Los Angeles. We underscore how federal labor law is inadequate to address unstable scheduling and we discuss retail worker organizing and the implications of time theft for labor policy and worker movements.